Graphene nanosheet and preparation method thereof
By using an iodate solution as the electrolyte solution and electrochemical anode peeling method, the graphene nanosheets were prepared, which solved the problems of high corrosion, high cost and many graphene defects in the electrochemical peeling process, and achieved the preparation of high-quality graphene nanosheets at low cost and high efficiency.
Patent Information
- Application Number
- CN202311213691.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
During the electrochemical peeling of graphene, the electrolyte is corrosive, costly, and has many graphene defects, which affects its conductivity.
Graphene nanosheets were prepared by electrochemical anode peeling method using an iodate solution to reduce corrosion, reduce costs, and improve the quality and electrochemical properties of graphene.
The high-quality graphene nanosheets are prepared at low cost and efficiently, reducing the corrosion and cost in the electrochemical peeling process and improving the conductivity of graphene.
Smart Images

Figure CN119660726A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene, and in particular relates to a graphene nanosheet and a preparation method thereof. Background Art
[0002] Graphene is a sp 2 A material in which hybrid connected carbon atoms are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Graphene has excellent optical, electrical, and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine, and drug delivery. It is considered to be a revolutionary material in the future. However, it is still a challenge to achieve green, non-toxic, pollution-free, low-cost, large-scale preparation of easy-to-process graphene.
[0003] Electrochemical exfoliation is a new method for preparing graphene developed in recent years. It mainly uses an electric field to drive oppositely charged ions and mixtures to insert into graphite electrodes, expand and exfoliate the graphite interlayers to obtain graphene. The main advantages of this method are: the voltage and current can be precisely adjusted, the graphite exfoliation process is reproducible and operable; the electrolysis is usually carried out at room temperature or near room temperature. Therefore, electrochemical exfoliation of graphene is a promising preparation technology for low-cost large-scale production of high-quality graphene. According to the different exfoliation mechanisms, electrochemical exfoliation of graphene can be divided into electrochemical cathode exfoliation and electrochemical anode exfoliation. Since oxygen evolution reaction occurs at the anode during anodic exfoliation, the exfoliated graphene has a certain amount of oxygen-containing functional groups, so that the graphene can form a well-dispersed graphene dispersion in water or organic solvents such as NMP, DMF, etc. This dispersion is easy to process and can be dried or freeze-dried into powder with good redispersibility, so it can be applied in a wide range of fields.
[0004] At present, most electrolytes used for electrochemical exfoliation of graphene are highly soluble sulfates (Carbon 149 (2019) 213e221), halogen salts (ACS Appl. Mater. Interfaces 2017, 9, 24085-24099), organic systems (J. Am. Chem. Soc. 2011, 133, 8888-8891), ionic liquids (Carbon 84 (2015) 449-459) systems, etc. The graphene exfoliated from the sulfate system has a high oxygen content and many defects, which greatly affects the conductivity of the graphene. In addition, the amount of salt used is large and the cost is high. The ionic liquid system also involves high cost issues. The organic system and the halogen system are even more involved. The halogen anions will form a single substance that is separated from the system under a huge cell voltage, resulting in a continuous decrease in the salt content.
[0005] Therefore, developing a low-cost, non-corrosive inorganic salt aqueous solution system for electrochemical anodic stripping to prepare graphene has good application value. Summary of the invention
[0006] In view of this, the present invention provides a graphene nanosheet and a preparation method thereof, the main purpose of which is to solve the technical problems of corrosive electrolyte, high cost and many graphene defects during electrochemical stripping.
[0007] On the one hand, the present invention provides a method for preparing graphene nanosheets, comprising: using an iodate solution as an electrolyte, and electrochemically stripping a graphite-containing raw material to obtain graphene nanosheets.
[0008] The method of the present invention uses iodate solution as electrolyte, reduces corrosiveness, has low cost, high efficiency, simple operation, and is safe and controllable. The prepared graphene has high quality and high electrochemical performance.
[0009] Optionally, the iodate is selected from at least one of lithium iodate, potassium iodate, sodium iodate and ammonium iodate;
[0010] The iodate of the present invention can also be selected from the prior art according to actual needs.
[0011] Optionally, the concentration of the iodate solution is 0.01 to 10 mol / L.
[0012] Optionally, the concentration of the iodate solution is 0.01 mol / L to 7 mol / L.
[0013] Optionally, the concentration of the iodate solution is 1 mol / L to 6 mol / L.
[0014] Optionally, the concentration of the iodate solution is independently selected from any value among 0.01mol / L, 0.05mol / L, 0.1mol / L, 0.15mol / L, 0.2mol / L, 0.3mol / L, 0.5mol / L, 1mol / L, 1.6mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L or a range value between any two of the above points.
[0015] In the present invention, different concentrations of iodate are used as electrolytes to prepare graphene nanosheets with different oxygen contents, sheet diameters and numbers of layers.
[0016] Optionally, the iodate solution comprises water, iodate and an organic solvent.
[0017] Optionally, the organic solvent is selected from at least one of ethylene glycol, glycerol and nitriles.
[0018] Optionally, the graphite-containing raw material is cleaned with deionized water before being used as an electrochemical anode.
[0019] Optionally, the graphite-containing raw material is selected from at least one of microcrystalline graphite, graphite rods, natural flake graphite, graphite paper and graphite foil.
[0020] Optionally, the voltage applied during the electrochemical stripping is 2 to 20V.
[0021] Optionally, the voltage is independently selected from any value among 2V, 5V, 8V, 10V, 12V, 15V, 18V, 20V or a range of values between any two of the above points.
[0022] Optionally, the electrochemical anode stripping time is 5 minutes to 48 hours.
[0023] Optionally, the electrochemical anodic stripping time is 0.5 h to 5 h.
[0024] Optionally, the time of the electrochemical anodic stripping is independently selected from any value among 5 min, 20 min, 30 min, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 8 h, 10 h, 12 h, 18 h, 24 h, 30 h, 36 h, 42 h, 48 h, or a range value between any two of the above points.
[0025] Optionally, the temperature of the electrochemical anode stripping is 5-50°C.
[0026] Optionally, the temperature of the electrochemical anodic stripping is independently selected from any value of 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or a range between any two of the above points.
[0027] The voltage, stripping time, temperature, etc. in the electrochemical anodic stripping method of the present invention can be adjusted according to actual needs.
[0028] Optionally, in the electrochemical stripping, the electrochemical anode is a graphite-containing raw material, and the electrochemical cathode is a conductive electrochemically inert material.
[0029] Optionally, the electrochemical cathode material is selected from at least one of glassy carbon, platinum, graphite and nickel.
[0030] Optionally, the ratio of the area of the electrochemical anode immersed in the electrolyte to the area of the electrochemical cathode immersed in the electrolyte is 0.2-12.
[0031] Optionally, the ratio of the area of the electrochemical anode immersed in the electrolyte to the area of the electrochemical cathode immersed in the electrolyte is independently selected from any value among 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 or the range between any two of the above points.
[0032] Optionally, the horizontal distance between the electrochemical cathode and the electrochemical anode immersed in the electrolyte is 1 to 3 cm.
[0033] Optionally, the distance between the electrochemical cathode and the electrochemical anode is independently selected from any value among 1 cm, 1.1 cm, 1.2 cm, 1.3 cm, 1.4 cm, 1.5 cm, 1.6 cm, 1.7 cm, 1.8 cm, 1.9 cm, 2 cm, 2.1 cm, 2.2 cm, 2.3 cm, 2.4 cm, 2.5 cm, 2.6 cm, 2.7 cm, 2.8 cm, 2.9 cm, 3 cm, or a range between any two of the above points.
[0034] Optionally, the method further comprises: after electrochemical anode exfoliation of graphite, the exfoliation product is washed and ultrasonically dispersed to obtain graphene nanosheet slurry, and the slurry is dried to obtain graphene nanosheets.
[0035] Optionally, the washing method is selected from at least one of dialysis, centrifugation and filtration.
[0036] Optionally, the drying method is selected from at least one of natural air drying, normal pressure heating drying, vacuum drying, spray drying and freeze drying;
[0037] Optionally, the ultrasonic dispersion time is 1 h to 2 h.
[0038] Optionally, the ultrasonic dispersion time is independently selected from any value among 1 h, 1.2 h, 1.4 h, 1.5 h, 1.6 h, 1.8 h, 2 h, or a range between any two of the above points.
[0039] The present invention provides a specific method for preparing graphene nanosheets by electrochemical anode exfoliation of graphite, comprising the following steps:
[0040] An aqueous solution containing iodate is used as an electrolyte, a raw material containing graphite is used as an electrochemical anode, and a conductive electrochemically inert material is used as an electrochemical cathode;
[0041] The electrolyte, electrochemical anode and electrochemical cathode constitute an electrochemical circuit;
[0042] A voltage is applied between the electrochemical cathode and the electrochemical anode, and the electrochemical anode exfoliates graphite to prepare graphene nanosheets.
[0043] The method for preparing graphene nanosheets by electrochemical anodic exfoliation of graphite is achieved by the following steps: firstly, a soluble iodate is used as an electrolyte for exfoliation, a conductive material is used as a counter electrode connected to the negative electrode of a direct current power supply, graphite is used as a raw material and connected to the positive electrode of the direct current power supply, and an appropriate cell voltage is selected to perform electrochemical exfoliation under normal temperature and pressure conditions, and the exfoliated product is washed and ultrasonically dispersed to obtain a graphene nanosheet slurry, and then dried to obtain a graphene nanosheet powder.
[0044] In the present invention, "room temperature" refers to 10 to 45°C.
[0045] In a second aspect, the present invention provides a graphene nanosheet, which is prepared by the above-mentioned preparation method.
[0046] Optionally, the size of the graphene nanosheets is 0.5 to 200 μm.
[0047] Optionally, the number of layers of the graphene nanosheets is 1 to 7.
[0048] Optionally, the surface oxygen content of the graphene nanosheets is 10 to 20 at %.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] 1) The present invention provides a new method for preparing graphene nanosheets by electrochemical anodic exfoliation of graphite, and graphene nanosheets are successfully prepared using iodate as electrolyte.
[0051] 2) The method for preparing graphene nanosheets by electrochemical anodic exfoliation of graphite provided by the present invention is simple to operate, safe and controllable, low-cost and highly efficient.
[0052] 3) The present invention is relatively more environmentally friendly and has less corrosion to the electrochemical stripping device. It uses soluble iodate as electrolyte and electrochemical anode stripping of graphite to synthesize graphene nanosheets in one step. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is a slurry image of graphene nanosheets prepared in Example 1 of the present invention;
[0054] Figure 2 is a scanning electron microscope image of the graphene nanosheet prepared in Example 1 of the present invention;
[0055] Figure 3 is a transmission electron microscope image of the graphene nanosheet prepared in Example 1 of the present invention;
[0056] Figure 4 is an atomic force microscopic analysis image of the graphene nanosheet prepared in Example 1 of the present invention;
[0057] Figure 5 is an atomic force microscopic height distribution diagram of the few-layer graphene nanosheet prepared in Example 1 of the present invention;
[0058] Figure 6 This is a detailed X-ray photoelectron spectrum of the graphene nanosheet prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0059] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0060] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0061] The analysis method in the examples of this application is as follows:
[0062] SEM analysis was performed using a Quanta-200F scanning electron microscope.
[0063] TEM analysis was performed using a HT-7700 transmission electron microscope.
[0064] AFM analysis was performed using NanoWizard atomic force microscopy.
[0065] XPS analysis was performed using a Thermofisher Escalab 250Xi+ quasi-in-situ X-ray photoelectron spectrometer.
[0066] Example 1
[0067] Take 100 mL of 0.8 mol / L sodium iodate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium iodate, and the platinum cathode was completely immersed in the position below the interface of the sodium iodate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was carried out at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles was generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and sodium iodate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0068] Example 2
[0069] Take 100 mL of 0.5 mol / L sodium iodate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium iodate, and the platinum cathode was completely immersed in the position below the interface of the sodium iodate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was carried out at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles was generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and sodium iodate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0070] Example 3
[0071] Take 100 mL of 1 mol / L sodium iodate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium iodate, and the platinum cathode was completely immersed in the position below the interface of the sodium iodate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was carried out at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles was generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and sodium iodate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0072] Example 4
[0073] Take 100 mL of 2 mol / L potassium iodate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of potassium iodate, and the platinum cathode was completely immersed in the position below the interface of the potassium iodate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles was generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium iodate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0074] Example 5
[0075] Take 100 mL of 2.4 mol / L potassium iodate solution and put it into a 250 ml beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of potassium iodate, and the platinum cathode was completely immersed in the position below the interface of the potassium iodate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles was generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium iodate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0076] Example 6
[0077] Take 100 mL of 3.6 mol / L sodium iodate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium iodate, and the platinum cathode was completely immersed in the position below the interface of the sodium iodate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was carried out at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles was generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and sodium iodate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0078] Test Example 1 Morphology Characterization
[0079] Sample 1 is in the form of a slurry, such as Figure 1 As shown; the slurries of other samples are Figure 1 resemblance.
[0080] SEM image of sample 1, as shown Figure 2 As shown; Figure 2 The SEM images of other samples are similar to Figure 2 resemblance.
[0081] TEM image of sample 1, such as Figure 3 As shown; Figure 3 It shows that individual graphene nanosheets are only slightly stacked, and the graphene nanosheets are peeled off by electrochemical cathode. The TEM images of other samples are similar to Figure 3 resemblance.
[0082] Atomic force microscopy analysis of few-layer graphene of sample 1, as shown in Figure 4 As shown;
[0083] Figure 4It shows that the graphene nanosheets in sample 1 exist as single-layer or few-layer graphene nanosheets.
[0084] Atomic force microscopy height distribution of few-layer graphene of sample 1, as shown in Figure 5 As shown;
[0085] Figure 5 It shows that the graphene nanosheets in sample 1 exist as single-layer or few-layer graphene nanosheets.
[0086] Atomic force microscopy height distribution of few-layer graphene of sample 1, as shown in Figure 6 As shown;
[0087] Figure 6 It shows that the graphene nanosheets in sample 1 have an oxygen content of less than 20 at %.
[0088] Through the above-mentioned tests, the morphology and electrical properties of the graphene material prepared by electrochemical exfoliation using iodate solution as electrolyte in the present invention can meet the use requirements.
[0089] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing graphene nanosheets, characterized in that: The preparation method comprises: using an iodate solution as an electrolyte, and stripping a graphite-containing raw material through an electrochemical anode to obtain graphene nanosheets.
2. The method for preparing a graphene nanosheet according to claim 1, characterized in that: The iodate is selected from at least one of lithium iodate, potassium iodate, sodium iodate and ammonium iodate.
3. The method for preparing a graphene nanosheet according to claim 1, characterized in that: The concentration of the iodate solution is 0.01-10 mol / L.
4. The method for preparing a graphene nanosheet according to claim 1, characterized in that: The iodate solution comprises water, iodate and an organic solvent; the organic solvent is selected from at least one of ethylene glycol, glycerol and nitriles; Preferably, the graphite-containing raw material is selected from at least one of microcrystalline graphite, graphite rods, natural flake graphite, graphite paper and graphite foil.
5. The method for preparing a graphene nanosheet according to claim 1, characterized in that: The voltage applied during the electrochemical anodic stripping is 2 to 20V.
6. The method for preparing a graphene nanosheet according to claim 1, characterized in that: The time of the electrochemical anodic stripping is 5 minutes to 48 hours; the temperature of the electrochemical anodic stripping is 5 to 50°C.
7. The method for preparing a graphene nanosheet according to claim 1, characterized in that: In the electrochemical stripping, the electrochemical anode is a graphite-containing raw material, and the electrochemical cathode is a conductive electrochemically inert material; the conductive electrochemically inert material is selected from at least one of glassy carbon, platinum, graphite and nickel.
8. The method for preparing a graphene nanosheet according to claim 7, characterized in that: The ratio of the area of the electrochemical anode immersed in the electrolyte to the area of the electrochemical cathode immersed in the electrolyte is 0.2 to 12; Preferably, the horizontal distance between the electrochemical cathode and the electrochemical anode immersed in the electrolyte is 1 to 3 cm; Preferably, the method further comprises: after electrochemical anode exfoliation of graphite, the exfoliated product is washed and ultrasonically dispersed to obtain graphene nanosheet slurry, and the slurry is dried to obtain graphene nanosheets; Preferably, the washing method is selected from at least one of dialysis, centrifugation and filtration; The drying method is selected from at least one of natural air drying, normal pressure heating drying, vacuum drying, spray drying and freeze drying; The ultrasonic dispersion time is 1 to 2 hours.
9. A graphene nanosheet, characterized in that: The graphene nanosheet is prepared by the method for preparing a graphene nanosheet according to any one of claims 1 to 8.
10. The graphene nanosheet according to claim 9, characterized in that: The size of the graphene nanosheet is 0.5 to 200 μm; The number of layers of the graphene nanosheet is 1 to 7; Preferably, the surface oxygen content of the graphene nanosheets is 10 to 20 at %.
Citation Information
Patent Citations
Preparation method of graphene
CN103058174A
Method for preparing graphene
CN104773730A
Preparation method and application of iodine-doped graphene
CN106602064A
Method for preparing graphene oxide based on high-concentration inorganic saline solution stripping
CN110357087A
